2016
DOI: 10.1016/j.jnucmat.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of key physical properties for LaCl3 in molten eutectic LiCl–KCl by fitting cyclic voltammetry data to a BET-based electrode reaction kinetics model

Abstract: Understanding the electrochemical properties of rare earth elements is important for developing efficient techniques for separating rare earth elements from actinides recovered during the electrodeposition process. In this study the cyclic voltammetry for lanthanum in molten LiCl-KCl eutectic was recorded at 773 K for different scan rates and different bulk concentrations. A model accounting for mass transport, kinetics and adsorption was applied to analyze the experimental data via performing a nonlinear leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…This indicates that the concentration of La in the molten salt affects its apparent potential in the salt. In a more recent study conducted by Samin [25], it is demonstrated that the apparent potential of La is indeed affected by its concentration and the results are summarized in Table A - [21]. In more recent research, Tang and Pesic [24] reported activity coefficient of LaCl3 from 693 K to 813 K in Table A -9.…”
Section: Lanthanummentioning
confidence: 94%
See 1 more Smart Citation
“…This indicates that the concentration of La in the molten salt affects its apparent potential in the salt. In a more recent study conducted by Samin [25], it is demonstrated that the apparent potential of La is indeed affected by its concentration and the results are summarized in Table A - [21]. In more recent research, Tang and Pesic [24] reported activity coefficient of LaCl3 from 693 K to 813 K in Table A -9.…”
Section: Lanthanummentioning
confidence: 94%
“…Besides using the traditional CV analysis methods, we have also developed a BET model to determine formal potential, diffusion coefficient, transfer coefficient, and standard rate constant by fitting experimental CV data [25,49]. In the model, both oxidized (RE 3+ ) and reduced species (RE) concentration as a function of time and location is governed by diffusion equations:…”
Section: 2 Numerical Simulation Using Bet Modelmentioning
confidence: 99%
“…For instance, while obtaining experimental densities can be relatively straightforward, determining other important thermodynamic, transport, and structural (X-ray/neutron diffraction) properties can be a time-consuming and expensive endeavor. Moreover, even when experimental databanks exist for certain molten salts, uncertainties in the order of ±20% are common, posing obstacles in designing systems that utilize molten salts. Therefore, the development of theoretical techniques that are not limited by the constraints faced in experiments and can evaluate any arbitrary salt composition and temperature is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammetry (CV) is one electroanalytical technique that has been employed in the molten LiCl-KCl eutectic to investigate the electrochemical, diffusion, and kinetic behavior of solvated actinide and lanthanide chlorides [4,[13][14][15][16][17][18][19][20]. Actinide chloride data is more abundant, as actinides pose greater proliferation risk and are the main analytes of interest in the electrorefiner.…”
Section: Introductionmentioning
confidence: 99%